2021
DOI: 10.2478/ebtj-2021-0015
|View full text |Cite
|
Sign up to set email alerts
|

In silico analysis of selected components of grapefruit seed extract against SARS-CoV-2 main protease

Abstract: At the end of December 2019, first identified cases of Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) started emerging. Ever since the emergence of the first case of infection with SARS-CoV-2 or COVID-19, it became the hottest research topic of numerous studies, in which scientists are trying to understand the path of infection, transmission, replication and viral action, all in order of finding a potential cure or vaccine applying various fundamental principles and methodologies. Using in silico… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…209 In silico analysis showed that several components of grapefruit seed extract, including naringenin, bind with Mpro with a binding affinity of −8.2 kcal/mol. 195…”
Section: Nasal Spray Containing Xylitol Plus Gse (Grapefruit Seed Ext...mentioning
confidence: 99%
See 3 more Smart Citations
“…209 In silico analysis showed that several components of grapefruit seed extract, including naringenin, bind with Mpro with a binding affinity of −8.2 kcal/mol. 195…”
Section: Nasal Spray Containing Xylitol Plus Gse (Grapefruit Seed Ext...mentioning
confidence: 99%
“…Thus, the occurrence of Mpro only within SARS-CoV-2 and not in the host cell has focused attention on this as a possible inhibition site for COVID-19 treatment. [190][191][192][193][194][195] In a molecular docking study, aimed at identifying compounds found in medicinal plants with the potential to be COVID-19 Mpro inhibitors, NAR exhibited a binding energy of −7.99 kcal/mol when docking with Mpro (PDB:6LU7), suggesting NAR as a potential COVID-19 Mpro inhibitor. NAR forms H-bonds with the 6LU7 amino acid His164, Glu166, Asp187, and Thr190.…”
Section: Covid-19 Main Protease (Mpro) Inhibitionmentioning
confidence: 99%
See 2 more Smart Citations